Technical Advantage and economic analysis of spiral anchor foundation in desert area - Gan, Jingshuang; Li, Benliang; Liu, Quan; Liu, Fuhai; Wu, Hanqing (Transactions on Economics, Business and Management Research, 2024)
State grid corporation “Infrastructure Technology [2022] No.14”document spiral anchor application as a recommended application of technology, requirements for the application of engineering as far as possible, since then, spiral Anchor Foundation is widely used in tower foundation of transmission line engineering. Using desert, Gobi, desert and abandoned mines to build photovoltaic power plants has become the“14th five-year plan” new energy development priority, supporting the rapid development of power grid transmission projects, there are more and more overhead power lines across the desert. Compared with other types of foundation, spiral anchor foundation in desert area not only has higher feasibility in technology, but also has more obvious advantages in material consumption and environmental protection, in particular, it can realize the advantages of zero-concrete and zero-earthwork construction, greatly saving the project cost.